Efficiency Analysis of Sharia Commercial Banks (BUS) in Indonesia During 2015 – 2019 - M Iqbal Aenun Najib; Deden Dinar Iskandar (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Research purposes to analyze the efficiency of Islamic Commercial Banks in Indonesia during the period 2015 – 2019. The object of this research is Sharia Commercial Banks consisting of Bank Muamalat, BRI Syariah Bank, Mega Syariah Bank, Bukopin Syariah Bank, BNI Syariah Bank and BCA Syariah Bank. This study uses the Data Envelopment Analysis (DEA) method. The input variables used in this study are total assets, savings and other operational costs, while the output variables used are securities owned and other operating income. The results of the study show that BRI Syariah Bank and BNI Syariah Bank are inefficiency or inefficient, apart from these banks, namely Bank Muamalat, Bank Mega Syariah, Bank Syariah Bukopin, and Bank BCA Syariah are all efficient. The results of this study are expected to be able to contribute both theoretically and practically in increasing the efficiency of Islamic commercial banks. Keywords: Efficiency, Total Assets, Islamic Commercial Banks, DEA